Psychological predictors of youth track & field athletes` participation-motivations and relative elements - Zeng, H. Z.; Riveras, S.; Skelly, J.; Griffiths, D. (Research Quarterly for Exercise and Sport, 2020)
Background/Purpose: With the Youth Olympic Games has been held as a global sports event for the young athletes every four years, demanding on youth track/field athletes`(YTFAs`) research studies have become broader and deeper. This study explored: 1) the relationship between the YTFAs`participation motivations(PMs) and the relative elements (`Gender`,"Supports",and"Goal-settings"); and 2) the essential participation motivations that motivated the YTFAs participated in their practices and competitions. The"self-determination theory" was employed as the theoretical framework for guiding this study. Method: Participants were 133 YTFAs (age 15-18; 81boys, 52 Girls) from 12 public high schools of New York City. Youth Track/Field Athlete`s Participation Motivations and Relative Elements Questionnaire (YTFAPMREQ) was employed for data collection. The YTFAPMREQ consists of 27 items wherein eight items requested participants`general information. Nineteen items examined what reasons/factors (RF) motivated he/she participated in track/field practices and competition; each RF allowed him/her to respond in a five-point Likert-type scale (5 represents"Strongly-agree", and 1 represents"Disagree"). Major statistical techniques for data analyses are: 2 (Gender: male, female) x 2 (Supports: by-parents, by-school) x 2(Goal-settings: for-professional, for-amateur) x 2(Grades: 9-10, 11-12) factorial MANOVA, correla-tions, and multiple regressions. Analysis/Results: Findings included: A) top five mean scores among the 19 RFs are: RF3"For healthier whole body"(M = 4.436); RF11"to foster self-esteem"(M = 4.045); RF1"high technical content and unique value"(M = 4.023); RF2"for fun and not boredom"(M = 3.879); and RF8"to shape body"M = 3.857). B)The MANOVA discovered:"Supports"(?= .769,F = 1.664) did not reach a significantly different level but the"Gender","Goals-setting",and"Grades"did. C) Findings further revealed: (1) In the"Gender"ele-ment, 11 out of 19 comparisons showed significant differences with female scored higher than male; (2) although in overall the male scored lower than the females,but male scored higher in six out of 19 comparisons than the female; (3) In"Goal-settings"element, overall there are ten out of 38 comparisons reached significant differences level, in which six comparisons showed"for-professional"scored higher than `for-amateur`, and four comparisons indicated `for-amateur`scored higher than`for-professional". D) Correlation analysis showed significant positive correlation coefficients exist among the 19 PMs variables. E) Multiple regression analyses discovered positive pre-dictors for the three basic psychological needs (`Competence Needs`,`Relatedness Needs`, and`Autonomy Need`) according to the features of threepredictor models (by Gender, by Grades`, and by Goal-settings) of the participants. F) The MANOVAexposed: the`Supports`did not have significant impacts on the YTFAs"PMs, but the"Genders","Goal-settings",and "Grades"showed significant impacts on the YTFAs`PMs. Conclusions: The multiple regression analyses support that the three basic psychological needs contributed tothe YTFAs`participation motivations and their participation motivations can be effectively predicted. The findings of this study extend the literature in youth sports research by providing evidences about theYTFAs`participation motivations that have barely been covered in the previous youth sports studies.